2019
DOI: 10.1038/s41467-018-08206-6
|View full text |Cite
|
Sign up to set email alerts
|

A welding phenomenon of dissimilar nanoparticles in dispersion

Abstract: The oriented attachment of small nanoparticles (NPs) is recognized as an important mechanism involved in the growth of inorganic nanocrystals. However, non-oriented attachment of dissimilar NPs has been rarely observed in dispersion. This communication reports a welding phenomenon occurred directly between as-synthesized dispersions of single-component Au and chalcogenide NPs, which leads to the formation of asymmetric Au-chalcogenide hybrid NPs (HNPs). The welding of dissimilar NPs in dispersion is mainly dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…The welding process is driven by the instability of NCs and the diffusion of metal atoms on the common crystalline facets of neighboring NCs. [103,104] The early welding method based on oriented attachment is, however, largely limited to the same types of nanoparticles due to the requirement of lattice matching. [12,105,106] So far, there have been only a few works on welding of dissimilar nanoparticles through a nonoriented attachment mechanism.…”
Section: Other Synthetic Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The welding process is driven by the instability of NCs and the diffusion of metal atoms on the common crystalline facets of neighboring NCs. [103,104] The early welding method based on oriented attachment is, however, largely limited to the same types of nanoparticles due to the requirement of lattice matching. [12,105,106] So far, there have been only a few works on welding of dissimilar nanoparticles through a nonoriented attachment mechanism.…”
Section: Other Synthetic Strategiesmentioning
confidence: 99%
“…For example, multicomponent Au-chalcogenide hybrid nanostructures with specific shapes and morphologies have been formed through welding of dissimilar Au and chalcogenide nanoparticles. [104] After the mixture of citrate/ PEG-functionalized Au nanoparticles with Ag 2 S nanoparticles that are modified with bovine serum albumin (BSA), Au-Ag 2 S oligomer-like hybrid nanostructures are formed through weak electrostatic attraction between the dissimilar nanoparticles and repulsion between the same types of nanoparticles (Figure 6a). During the process, atom diffusion between the Au and Ag 2 S domain occurs and the hybrid nanostructures are subsequently welded.…”
Section: Other Synthetic Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many efforts have also been made to investigate the physical and chemical properties of the hybrid NCs [2,[35][36][37][38], and the results indicated that their properties are highly dependent on the size, shape, composition, and spatial distribution of each component [24,30,[39][40][41]. Therefore, a large number of schemes keep emerging towards synthesis of these hybrid nanostructures under the joint endeavours of the majority of scientific researchers [42][43][44][45][46]. Among them, seed-mediated selective growth of semiconductor shells based on metal nanocrystals has unique advantages, owing to abundant and controllable plasmon properties from the designed metal nanostructures [33,44,47,48].…”
mentioning
confidence: 99%